Comparative Study on Iron Content Detection by Energy Spectral CT and MRI in MDS Patients - Zhang, Yao; Xiao, Chao; Li, Jing; Song, Lu-xi; Zhao, You-shan; Han, Shuang; Li, Zhao-wei; Guo, Cha; Zhao, Jun-gong; Chang, Chun-kang (Frontiers in Oncology, 2021)
Objective The purpose of this study was to identify the difference between dual energy spectral computed tomography (DECT) and magnetic resonance imaging (MRI) used to detect liver/cardiac iron content in MDS patients with different adjust serum ferritin (ASF) levels. Method Liver and cardiac iron content were detected by DECT and MRI. Patients were divided into different subgroups according to the level of ASF. The receiver operating characteristic curve (ROC) analysis was applied in each subgroup. The correlation between iron content detected by DECT/MRI and ASF was analyzed in each subgroup. Result ROC curves showed liver virtual iron content( LVIC) Az was significantly less than liver iron concentration (LIC) Az in the subgroup with ASF<1000 ng/ml. There was no significant difference between LVIC Az and LIC Az in the subgroup with 1000≤ASF<2500 ng/ml and 2500≤ASF<5000 ng/ml. LVIC Az was significantly higher than LIC Az in the subgroup with 5000≤ASF ng/ml. In patients undergoing DECT and MRI examination on the same day, ASF was significantly correlated with LVIC whereas no significant correlation was observed between ASF and LIC. After removing the data of ASF > 5000 mg/L in LIC, LIC became correlated with ASF. There was not significantly different between the subgroup with 2500≤ ASF<5000ng/ml and 5000 ng/ml ≤ASF in LIC expression. Furthermore, both of LIC and LVIC had significant correlations with ASF in patients with ASF < 2500ng/ml, while LVIC was still correlated with ASF.LIC was not correlated with ASF in patients with 2500ng/ml≤ ASF. Moreover, neither cardiac VIC nor myocardial iron content (MIC) were correlated with ASF in these subgroups. Conclusion MRI and DECT were complementary to each other in iron detection. In MDS patients with high iron content, such as ASF ≥5000ng / ml, DECT was more reliable than MRI in the assessment of iron content. But in patients with low iron content, such as ASF < 1000 ng / ml, MRI is more reliable than DECT. Therefore, for sake of evaluating the iron content more accurately, the appropriate detection method can be selected according to ASF.